„Cierpiąca pałuba”, czyli rozważania Brunona Schulza i Heinricha Kleista o materii - Nikitina, Ekaterina (Postscriptum Polonistyczne, 2020)
The article presents Bruno Schulz’s and Heinrich Kleist considerations on matter. A comparative approach enables a new interpretation of Traktat o manekinach by Schulz and of some selected works by Kleist. The author ponders about the role of elpis, around which the human world is created. The Greek word: elpis, contains a whole parable about a hope which has stood up to nonexistence, darkness, a lack of form. A human being turns out to be forced to create, knead matter, because his life depends on it. By shaping things he gives reality to his own world that may disappear at any time. Both reflected upon authors, Schulz and Kleist, choose two different paths to contact with matter and they inscribe it – together with a human being – into a philosophical thought that goes far beyond simple the “living” – “lifeless” opposition.